Effects on RF Performance for AlGaN/GaN HEMT on Si Substrate with AlGaN Buffer Engineering. (7th March 2023) - Weng, You-Chen; Hsu, Heng-Tung; Tsao, Yi-Fan; Panda, Debashis; Huang, Hsuan-Yao; Kao, Min-Lu; Lan, Yu-Pin; Chang, Edward Yi; Lee, Ching-Ting
Abstract : In this paper, we demonstrate the AlGaN/GaN high electron mobility transistors (HEMTs) on Si substrate using an AlGaN back-barrier (BB) and super-lattice (SL) buffer to achieve high breakdown and low current collapse (CC) properties for Radio-frequency (RF) applications. The HEMTs also demonstrated low initial vertical leakage current, high thermal stability, and smaller drain-lag with reduced leakage currents as compared to the devices using step-graded (SG) AlGaN buffer. Also, the device showed improved RF performances with higher f T and f max as compared to the devices with SG buffer.